Experimental-Numerical Assessment of Mechanical Behavior of Laboratory-Made Steel and NiTi Shape Memory Alloy Wire Ropes - Peyman Narjabadifam; Neda Fazlalipour; Somayeh Mollaei; Mohammad Momeni; Ali Saman Watandoust; Mahdi Chavoshi; Alireza Babaeian Amini; Farshad Karazmay (Buildings, 2024)
The mechanical behaviors of laboratory-fabricated steel and superelastic shape memory alloy (SMA) wire ropes are assessed in this study through a comprehensive approach encompassing both experimental investigations and finite element (FE) numerical simulations. The assessment of steel wire ropes involves experimental scrutiny under sinusoidal cyclic loading and natural earthquake loading conditions. In parallel, SMA wire ropes’ behaviors are analyzed utilizing FE simulations employing the widely acknowledged ABAQUS software version 2020. The validation of all numerical simulations is undertaken against the experimentally observed behaviors. Moreover, full-scale steel wire ropes are subjected to shaking table tests to validate the simulations, facilitating a comparative analysis between the mechanical responses of SMA and steel wire ropes. The findings demonstrate that SMA wire ropes exhibit superelastic behavior akin to SMA wires, with marginal variations in overall response observed across distinct configurations, akin to steel wire ropes. Furthermore, augmenting the helix angle of SMA wire ropes results in reduced stress and increased strain when exposed to the El Centro earthquake scenario. Nevertheless, the mechanical response of SMA wire ropes closely mirrors that of a single wire.